2013
DOI: 10.1109/tasl.2013.2250960
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Speech Dereverberation From Probabilistic Perspective for Time Varying Acoustic Transfer Function

Abstract: A dereverberation technique has been developed that optimally combines multichannel inverse filtering (MIF), beamforming (BF), and non-linear reverberation suppression (NRS). It is robust against acoustic transfer function (ATF) fluctuations and creates less distortion than the NRS alone. The three components are optimally combined from a probabilistic perspective using a unified likelihood function incorporating two probabilistic models. A multichannel probabilistic source model based on a recently proposed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…We recently found that steering vector estimation by clustering the time-frequency components of the observation vectors performs well as regards noise reduction of real-world recordings [11,12]. The clustering is performed by taking a cue from the spatial correlation matrix of each speaker location [13][14][15], which is realized by modeling the timefrequency components of the microphone observation vectors with a complex GMM (CGMM). This paper describes the application of our above-mentioned MVDR beamforming scheme to real recordings of multi-speaker meeting conversations.…”
Section: Introductionmentioning
confidence: 99%
“…We recently found that steering vector estimation by clustering the time-frequency components of the observation vectors performs well as regards noise reduction of real-world recordings [11,12]. The clustering is performed by taking a cue from the spatial correlation matrix of each speaker location [13][14][15], which is realized by modeling the timefrequency components of the microphone observation vectors with a complex GMM (CGMM). This paper describes the application of our above-mentioned MVDR beamforming scheme to real recordings of multi-speaker meeting conversations.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithms of the second class are proposed, e. g., in [6][7][8][9], where the acoustic system was described using an auto-regressive model. The approach proposed in [6] estimates the clean speech for a single source based on multichannel linear prediction by enhancing the linear prediction residual of the clean speech.…”
Section: Introductionmentioning
confidence: 99%
“…The approach proposed in [6] estimates the clean speech for a single source based on multichannel linear prediction by enhancing the linear prediction residual of the clean speech. In [7][8][9], the received signal is expressed using an autoregressive model and the regression coefficients are estimated from the observations. The clean speech is then estimated using the regression coefficients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations